Distribution and occurrence of microsporidian pathogens of the willow flea beetle, Crepidodera aurata (Coleoptera: Chrysomelidae) in North Turkey - Yaman, Mustafa; Algi, Gonul; Guner, Beyza Gonca; Unal, Sabri (This journal is published jointly by the Entomological Society of Finland, the Lepidopterological Society of Finland, the Societas Entomologica Helsingforsiensis and the Entomological Club of the Zoological and Botanical Society of Turku., 2015)
In this study, microsporidian pathogens in Crepidodera aurata populations were investigated. Totally 1,728 C. aurata adults were examined for microsporidian pathogens and 78 of them were found to be infected. Two species of microsporidia; Microsporidium sp.1 and Microsporidium sp.2 were observed in the C. aurata populations from ten localities in North Turkey. They show considerable difference from each other in the spore morphology and dimension, infection rate and host locality. The spores of Microsporidium sp.1 were oval in shape and measured from 3.66 to 5.66 µm in length and from 1.35 to 2.22 µm in width (n=50). The spores of Microsporidium sp. 2 were slightly curled and measured from 2.44 to 3.55 µm in length and from 1.25 to 1.55 µm in width (n=50). These microsporidia were recorded from C. aurata for the first time. Here we present occurrence and distribution of two microsporidia in C. aurata populations as natural potentially suppressing factors.